Theory and practice: remote classes pandemic - Colombo, Macri; Carvalho, Denize Piccolotto; Silva, Karina Goncalves Teixeira da; Varela, Ulysses Nascimento (Comunicação & Educação, 2023)
This experience report explore the remote classes teaching implemented by a Social Communication program from a private university in Manaus, during the covid-19 pandemic, to show the confrontation between theory and practice within higher education, at a time when the world was forced to live in total or partial social isolation – which leads us, first of all, to understand the issue between theory and practice before the pandemic. Ethnography, field research with participatory observation and interviews, based on Morin, Bauman, among others, act as its theoretical framework. Results show that despite efforts to continue theoretical and practical teaching, there is still no definitive answer to this problematic exists, with or without the pandemic.